Spontaneous Cerebrospinal Fluid Rhinorrhea: Association with Body Weight and Imaging Data - Quatre, Raphaële; Attye, Arnaud; Righini, Christian Adrien; Reyt, Emile; Giai, Joris; Schmerber, Sébastien; Karkas, Alexandre (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objective Spontaneous cerebrospinal fluid rhinorrhea (SCSFR) might be the only clinical manifestation of idiopathic intracranial hypertension (IIH), which has been historically related to overweight. Our goal was to search for an association between SCSFR and increased body weight on the one hand and SCSFR and imaging findings suggestive of IIH on the other hand.Materials and Methods We retrospectively collected clinical and radiological data of patients operated on endoscopically for SCSFR in our institution from 1993 to 2013. Analyzed factors were body mass index (BMI), extended sphenoid sinus pneumatization on computed tomography, and empty sella and distention of the optic nerve sheath on magnetic resonance imaging.Results There were 15 patients: 8 females/7 males; mean age 50 years. Primary surgical success rate was 86.7%. Regarding body weight, 80% were overweight (BMI ≥ 25) versus 32% in the French general population (p < 0.001). Among patients with SCSFR, 20% were obese (BMI ≥ 30) versus 15% in French individuals without SCSFR (p = 0.483). Increased pneumatization of sphenoid sinuses was observed in 92.9 versus 27.5% in the general population (p < 0.0001). Empty sella was found in 46.2 versus 3% in the general population (p < 0.00001). Dilation of the optic nerve sheath was observed in 46.2 versus 15% in the general population (p < 0.01).Conclusion We found statistically significant associations between SCSFR and overweight, increased pneumatization of sphenoid sinuses, empty sella, and dilation of optic nerve sheath, but not with obesity, which did not have any additional impact of CSF leak than did overweight.
Keywords: spontaneous cerebrospinal fluid rhinorrhea; intracranial pressure; sphenoid sinus; pneumatization; empty sella; optic nerve sheath